Influence of quick massage and pilates on the occupational health of workers of a private value securities network agency: A clinical, controlled, randomized and blind study - de Oliveira, Renata Michele Ângelo; Ferreira, Mônica Beatriz; Santos, Gabriela Xavier; Barbosa, Danillo; Kerppers, Ivo Ilvan (Clinical and Biomedical Research, 2018)
Introduction: This study aims to analyze the influence of quick massage and pilatespilates on bank employees. The project was sent to the Research Ethics Committee and obtained a favorable opinion (1,045,371 / 2015). Methods: It is a clinical, controlled, randomized, and blind study. The study had had initially involved 70 employeesparticipants, but only 50 were included. They were divided into 3 groups: quick massage group (n = 20), ppilates group (n = 20) and control group (n = 10). They were evaluated with experimental times of 3, 6 and 9 months and the protocol was applied 3 times per week. Results: The results of the present study were presented in standard deviation and mean of all groups, then a one-way analysis of the variance was performed, obtaining a value of P <0.0198, being considered significant. However, it is noted that when presenting the detailed data of each group (mean and standard deviation) it is observed that the group which received the quick massage had a small advantage.: (6 months) 4.03 ± 0.82, (12 months) 3.43 ± 1.15 and pilatespilates group (3 months) 6.21 ± 1.98016, (6 months) 4.26 ± 0.57873 (9 months) 4.14 ± 0.63. Conclusions: The quick massage techniques and the pilatespilates protocol have shown great potential in reducing anxiety, depression and fatigue. KEY-WORDS: Occupational health; worker health; pilatespilates and ergonomics